The intersection between DNA damage response and cell death pathways - Nowsheen, S.; Yang, E.S. (Experimental Oncology, 2012)
Apoptosis is a finely regulated process that serves to determine the fate of cells in response to various stresses. One such stress is DNA damage, which not only can signal repair processes but is also intimately involved in regulating cell fate. In this review we examine the relationship between the DNA damage/repair response in cell survival and apoptosis following insults to the DNA. Elucidating these pathways and the crosstalk between them is of great importance, as they eventually contribute to the etiology of human disease such as cancer and may play key roles in determining therapeutic response. This article is part of a Special Issue entitled “Apoptosis: Four Decades Later”.